CVFEM for Multiphase Flow with Disperse and Interface Tracking, and Algorithms Performances. (December 2015) - Milanez, M.; Naterer, G. F.; Popplewell, N.; Venn, G.; Richardson, G.
A Control-Volume Finite-Element Method (CVFEM) is newly formulated within Eulerian and spatial averaging frameworks for effective simulation of disperse transport, deposit distribution and interface tracking. Their algorithms are implemented alongside an existing continuous phase algorithm. Flow terms are newly implemented for a control volume (CV) fixed in a space, and the CVs' equations are assembled based on a finite element method (FEM). Upon impacting stationary and moving boundaries, the disperse phase changes its phase and the solver triggers identification of CVs with excess deposit and their neighboring CVs for its accommodation in front of an interface. The solver then updates boundary conditions on the moving interface as well as domain conditions on the accumulating deposit. Corroboration of the algorithms' performances is conducted on illustrative simulations with novel and existing Eulerian and Lagrangian solutions, such as (-) other, i. e. external methods with analytical and physical experimental formulations, and (-) characteristics internal to CVFEM.